2023
DOI: 10.28991/hef-2023-04-02-08
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Self-Determined Motivation in Exercise: A Systematic Review and Meta-analysis

Truong Thanh Nam,
Cua Ngoc Le,
Doan Hoang Phu
et al.

Abstract: systematic review and meta-analysis to assess associations between types of self-determined motivation in exercise with selected parameters of studies using Behavioral Regulation in Exercise Questionnaires (BREQs). Following PRISMA 2020 guidelines, we screened 244 studies from PubMed, ScienceDirect, and Scopus against criteria and selected 43 articles for qualitative synthesis. Of those, 40 studies reporting mean scores and standard deviations of six regulations of BREQs, representing self-determined motivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Furthermore, prior research concentrated on validating motivation scales in diverse workout environments, including public areas [25,31,39], academic institutions [37,38], medical settings [40,41], and gym and sports facilities [42][43][44], where those engaged in exercise have consistently reported higher motivation levels compared to other exercise settings. This strong positive association has also been linked to long-term exercise adherence [45]. When utilizing the same measuring instruments, however, prior research has not revealed significant variations in the specific items of exercise motives in the scale's construction for individuals who work out in fitness facilities as opposed to other settings.…”
Section: Intrinsic Motivationmentioning
confidence: 99%
“…Furthermore, prior research concentrated on validating motivation scales in diverse workout environments, including public areas [25,31,39], academic institutions [37,38], medical settings [40,41], and gym and sports facilities [42][43][44], where those engaged in exercise have consistently reported higher motivation levels compared to other exercise settings. This strong positive association has also been linked to long-term exercise adherence [45]. When utilizing the same measuring instruments, however, prior research has not revealed significant variations in the specific items of exercise motives in the scale's construction for individuals who work out in fitness facilities as opposed to other settings.…”
Section: Intrinsic Motivationmentioning
confidence: 99%
“…Engaging in diverse activities within the fitness environment, coupled with commitment-building strategies and bolstering encouragement from both staff and fellow members, serves to enhance the overall exercise experience, thereby nurturing a conducive atmosphere for sustained participation [5]. Interestingly, findings of a recent systematic review indicated that FC members reported higher motivation levels compared to those who exercised in other settings [16], such as public areas [17], academic institutions [18], and healthcare facilities [19,20].…”
Section: Introductionmentioning
confidence: 99%